وجه الحاجةإلى أنثروبولوجيا فلسفية عربية معاصرة - عقيبي, لزهر (Changement Social; No 03 (2017): مجــــلة التغير الاجتماعي, 2018)
The rooting of philosophicalanthropologyappearitsGermancharacter, based on the search for a place for man in the world, with Schiller, Plesner and Kahlen. Scientific and appliedanthropology descends from the Anglo-Saxon and French tradition, whichbeginswithBoaz, Fraser and Levi Strauss. However, the reception of thesetwo types of anthropology in Arabthought, and theirspread in the fields of highereducation, privatecenters and journals,notneed to beprovedtoday. But, thisspreadbegan to generatewidespreadcriticism of philosophicalanthropology, based on itsphilosophicaltheoriesthat do not reflect the identity or status of Arab man, as well as criticism of scientific and appliedanthropologybecause of their association with colonial and racisttendencies and theirinability to express the identity of the total Arabman,according to the logic of itsScientificresearche on partial issues. The Arab reality adds to thisepistemological situation an ontological dimension of the fragility of the status of the Arab man, hisquestioning of hisidentity, his place, hisabilities and hiswill to emancipation, whichrequires the establishment of an Arabphilosophicalanthropology..